2012
DOI: 10.1111/j.1460-9568.2012.08164.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor endplate disease affects neuromuscular junction maturation

Abstract: Postnatal formation of the neuromuscular synapse requires complex interactions among nerve terminal, muscle fibres and terminal Schwann cells. In motor endplate disease (med) mice, neuromuscular transmission is severely impaired without alteration of axonal conduction and a lethal paralytic phenotype occurs during the postnatal period. The med phenotype appears at a crucial stage of the neuromuscular junction development, corresponding to the increase in terminal Schwann cell number, the elimination of the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
(122 reference statements)
0
14
0
Order By: Relevance
“…It was recently reported that the neuronal and muscular components of the NMJ are defective in Scn8a −/− null mice (Caillol et al, 2012). The null NMJs lack the characteristic “pretzel” shape of the mature neuromuscular junction and the nerve terminals fail to develop complex arborization.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that the neuronal and muscular components of the NMJ are defective in Scn8a −/− null mice (Caillol et al, 2012). The null NMJs lack the characteristic “pretzel” shape of the mature neuromuscular junction and the nerve terminals fail to develop complex arborization.…”
Section: Resultsmentioning
confidence: 99%
“…(Bitplane, South Windsor, CT, USA) was used to analyze Z-stacked images for volume measure-ment of synaptic vesicles and postsynaptic endplate as previously conducted [33, 56]. Synaptic vesicles targeted by mouse anti-SV2 stained with Alexa Fluor 488-conjugated secondary antibody and postsynaptic AChR endplates stained with Alexa Fluor 555 α-BTX, were rendered in 3D based on fluorescent intensity using the surface-rendering module as previously described [33, 56, 57]. The mouse anti-SV2 antibody is highly specific for the binding of synaptic vesicles and it has been widely used for the staining of synaptic vesicles in other studies [33, 52, 56].…”
Section: Methodsmentioning
confidence: 99%
“…Synaptic vesicles targeted by mouse anti-SV2 stained with Alexa Fluor 488-conjugated secondary antibody and postsynaptic AChR endplates stained with Alexa Fluor 555 α-BTX, were rendered in 3D based on fluorescent intensity using the surface-rendering module as previously described [33, 56, 57]. The mouse anti-SV2 antibody is highly specific for the binding of synaptic vesicles and it has been widely used for the staining of synaptic vesicles in other studies [33, 52, 56]. Interactive histogram based volumetric pixels was used for thresholding of both SV2 and AChR labelling in order to accurately render 3D solid reconstructions without creating artifacts [33, 57].…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence has demonstrated impaired neuromuscular transmission in presymptomatic (4–6 weeks old) ALS mice compared to age-matched controls (Rocha et al, 2013). Impaired synaptic transmission and other electrophysiological changes in electrical excitability or conduction velocity disrupt the necessary interactions between the nerve terminal, muscle fibers and TSCs required for appropriate postnatal formation of the NMJ, which can lead to a delay in maturation of the NMJ in presymptomatic animals (Blijham et al, 2007; Van Zundert et al, 2008; Caillol et al, 2012). During development, appropriate electrical activity is essential to get the correct distribution of the acetylcholine receptors (AChR) on the muscle cell membrane for NMJ maturation at that location (Goldman et al, 1988), thus one could speculate that the abnormal age-appropriate activity seen at the NMJ of presymptomatic ALS mice could alter the subcellular localization of the AChRs and cause a destabilization of the affected NMJ.…”
Section: Distinctive Axonal And/or Synaptic Features That Could Initimentioning
confidence: 99%